Comparison of Postoperative Analgesic Effects Between Nalbuphine and Fentanyl in Children Undergoing Adenotonsillectomy: A Prospective, Randomized, Double-Blind, Multicenter Study - Chen, Fang; Wang, Cheng-Yu; Zhang, Jianmin; Wang, Fang; Zhang, Mazhong; Gu, Hongbin; Song, Xingrong; Chen, Jia; Li, Yang; Cai, Yu-Hang; Li, Jun; Lian, Qing-Quan; et al. (Frontiers in Pharmacology, 2020)
Objective: There is no universal agreement on optimal pharmacological regimens for pain management during surgeries. The aim of this study to compare the postoperative analgesic effects of nalbuphine with fentanyl in children undergoing adenotonsillectomy. Design, Setting, Participants: We conducted a prospective, randomized, double-blind, non-inferiority and multicenter trial in 311 patients admitted to four different medical facilities in China from October 2017 to November 2018. Main Outcome Measure: The primary outcome was postoperative pain score. The secondary outcomes were as follows: the numbers of patients who developed moderate or severe pain (FLACC ≥4 points); time to first rescue analgesic top up and the actual number of rescue pain medicine given in pain control in post-anesthesia care unit (PACU), and additional analgesics requirement (received ≥2 rescue analgesics or/and other analgesics except study medications administered in PACU and ward); emergence and extubation time; Waking up time; time of PACU stay, and other side effects (desaturation, nausea/vomiting etc.). Results: A total of 356 children were screened and 322 patients were randomized. The mean age was 5.8 (5.5, 6.1) in the nalbuphine group and 5.6 (5.3, 5.8) in the fentanyl group (p = 0.2132). FLACC score of nalbuphine group was lower than that of fentanyl group upon patients' arrival at PACU (p < 0.05). The time to first required rescue dose of pain drug for nalbuphine group was longer than for the fentanyl group (2.5 vs 1.2 h, p < 0.0001). Only one patient (0.6%) in nalbuphine group presented a slow respiratory rate (RR) at 9/min while 29 patients (18.5%) in fentanyl group developed slow RR ≤10/min in PACU. Meanwhile, SpO2 was lower in the fentanyl group at 10 min after patients’ arrival in PACU (p < 0.05). The other profiles observed from these two drug groups were similar. Conclusion: Nalbuphine provided better pain relief with minimal respiration depression than fentanyl in children undergoing Adenotonsillectomy.